Imports into NIgeria classified by end-use 1958 - 1966 (Lagos: Federal Office of Statistics, 1967)
The present classification is much less detailed than the classification by the Economic Categories prepared by the Statistical Office of the United Nations
osc 20/05/2019
Arch.
Keywords: Imports; Trade; External trade-statistics; Nigeria